Kalyāṇasaugandhikaṃ : Āṭṭakkatha - Kōṭṭayattu Tampurān (Sāhityapṟavarttaka Sahakaraṇasaṅghaṃ : Nāṣanal Bukksṯāḷ, 1973)
Text, with interpretive notes, of a libretto for Kathakali, depicting an episode from the Mahābhārata.